Associations between everyday discrimination and sleep quality and duration among African-Americans over time in the Jackson Heart Study. Issue 12 (1st July 2021) - Johnson, Dayna A; Lewis, Tené T; Guo, Na; Jackson, Chandra L; Sims, Mario; Wilson, James G; Diez Roux, Ana V; Williams, David R; Redline, Susan
Abstract: Study Objectives: African-Americans have a high burden of poor sleep, yet, psychosocial determinants (e.g. discrimination) are understudied. We investigated longitudinal associations between everyday discrimination and sleep quality and duration among African-Americans ( N = 3404) in the Jackson Heart Study. Methods: At Exam 1 (2000–2004) and Exam 3 (2008–2013), participants completed the Everyday Discrimination Scale, rated their sleep quality (1 = poor to 5 = excellent), and self-reported hours of sleep. A subset of participants ( N = 762) underwent 7-day actigraphy to objectively measure sleep duration and sleep quality (Sleep Exam 2012–2016). Changes in discrimination were defined as low stable (reference), increasing, decreasing, and high stable. Within-person changes in sleep from Exam 1 to Exam 3 were regressed on change in discrimination from Exam 1 to Exam 3 while adjusting for age, sex, education, income, employment, physical activity, smoking, body mass index, social support, and stress. Results: At Exam 1, the mean age was 54.1 (12.0) years; 64% were female, mean sleep quality was 3.0 (1.1) and 54% were short sleepers. The distribution of the discrimination change trajectories were 54.1% low stable, 13.5% increasing, 14.6% decreasing, and 17.7% were high stable. Participants who were in the increasing (vs. low stable) discrimination group had greater decrease in sleep quality. There was no association between change in discrimination and change in sleep duration. Among Sleep Exam participants, higher discrimination was cross-sectionally associated with shorter self-reported sleep duration, independent of stress. Conclusion: Discrimination is a unique stressor for African-Americans; thus, future research should identify interventions to reduce the burden of discrimination on sleep quality.